2022
DOI: 10.3389/fcvm.2022.1015983
|View full text |Cite
|
Sign up to set email alerts
|

Adverse association of epicardial adipose tissue accumulation with cardiac function and atrioventricular coupling in postmenopausal women assessed by cardiac magnetic resonance imaging

Abstract: BackgroundThis study aims to investigate the association of epicardial adipose tissue (EAT) accumulation with cardiac function and atrioventricular coupling in a cohort of postmenopausal women assessed by cardiac magnetic resonance imaging (CMR).Materials and methodsOverall, 283 postmenopausal women (mean age 61.5 ± 9.1 years) who underwent CMR examination were enrolled. Participants were classified into four groups by the quartile of EAT volume. EAT volume was quantified on short-axis cine stacks covering the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous clinical studies have reported that postmenopausal women tend to have expanded PFV, which can lead to cardiac and coronary abnormalities regardless of age, hypertension, diabetes, dyslipidemia, menopausal age, and BMI. The deleterious effects of increased pericardial fat deposition could be a result of systemic inflammation caused by altering the balance of secreting adipokines and cytokines toward pro‐atherogenic and proinflammatory conditions through the paracrine and vasocrine routes 8,9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical studies have reported that postmenopausal women tend to have expanded PFV, which can lead to cardiac and coronary abnormalities regardless of age, hypertension, diabetes, dyslipidemia, menopausal age, and BMI. The deleterious effects of increased pericardial fat deposition could be a result of systemic inflammation caused by altering the balance of secreting adipokines and cytokines toward pro‐atherogenic and proinflammatory conditions through the paracrine and vasocrine routes 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…The deleterious effects of increased pericardial fat deposition could be a result of systemic inflammation caused by altering the balance of secreting adipokines and cytokines toward pro‐atherogenic and proinflammatory conditions through the paracrine and vasocrine routes. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%